2016
DOI: 10.4041/kjod.2016.46.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of midpalatal miniscrew-assisted maxillary molar distalization patterns with simultaneous use of fixed appliances: A preliminary study

Abstract: Skeletal anchorage-assisted upper molar distalization has become one of the standard treatment modalities for the correction of Class II malocclusion. The purpose of this study was to analyze maxillary molar movement patterns according to appliance design, with the simultaneous use of buccal fixed orthodontic appliances. The authors devised two distinct types of midpalatal miniscrew-assisted maxillary molar distalizers, a lingual arch type and a pendulum type. Fourteen patients treated with one of the two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(30 reference statements)
0
14
0
1
Order By: Relevance
“…3,4,23,24 They have been marked by untoward side effects including extrusion, distal tipping, and the distal rotation of the maxillary first molars. [25][26][27][28] Previously, the treatment effects of a single buccally placed miniscrew on each side resulted in 1.4 to 2.0 mm of molar distalization and 1 mm intrusion with approximately 3.58 of distal tipping. 10 In the current study, the miniscrew group showed 2.0 mm of Recently, Bechtold et al 11 demonstrated a difference in the distalization pattern depending on the number of miniscrews.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,23,24 They have been marked by untoward side effects including extrusion, distal tipping, and the distal rotation of the maxillary first molars. [25][26][27][28] Previously, the treatment effects of a single buccally placed miniscrew on each side resulted in 1.4 to 2.0 mm of molar distalization and 1 mm intrusion with approximately 3.58 of distal tipping. 10 In the current study, the miniscrew group showed 2.0 mm of Recently, Bechtold et al 11 demonstrated a difference in the distalization pattern depending on the number of miniscrews.…”
Section: Discussionmentioning
confidence: 99%
“…the other hand, the process of maxillary teeth distalization with OMI anchorage is completely different from the conventional distalization technique previously reported. 7 8 9 10 11 12 A two-stage method was frequently used to distalize the maxillary teeth during nonextraction treatment of Class II patients with intraoral distalizing appliances. In the first stage, the maxillary molars moved distally, but loss of anchorage often occurred during molar distalization, which is characterized by mesial movement of the premolars and flaring of the anterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic mini-implants (OMIs), known as temporary anchorage devices, were introduced in clinical orthodontics to prevent loss of anchorage and could have specific advantages for nonextraction treatment by providing absolute anchorage. 12 13 14 Their ability to retract the whole dentition can minimize any adverse reciprocal movement and maximize the efficiency of treatment. 1 15 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 The introduction of miniscrew implants made skeletal anchorage more easily accessible for the orthodontist. 16 Miniscrew implants can be loaded directly 15,17 or through scaffolding 18,19 and have been shown to enable distal movement of the molars and premolars at the same time, 20,21 causing minimal distal tipping of the molars 21,22 which suggests high stability. However, throughout a lifetime, permanent molars exhibit mesial migration, 23 attributed to the anterior component of force, which is explained to result from mesial inclination of teeth.…”
Section: Introductionmentioning
confidence: 99%